Differentiation of hydrochlorothiazide-induced dermatitis from stasis dermatitis. Issue 9 (20th September 2022) - Abdelwahab, Rewan; Tangalos, Eric G; Matulis, John
Abstract : A woman in her 60s with a history of hypertension and stasis dermatitis presented to a primary care clinic with a bilateral, erythematous rash on the legs, stomach, and chest. Photosensitive rash and dermatitis may be caused by many conditions. Hydrochlorothiazide-induced dermatitis is a rare side effect of thiazide diuretics. Early identification of sulfa-sensitivity and photoallergic or phototoxic reaction is essential to accurate diagnosis and treatment of photosensitive dermatitis. Soliciting a targeted history is essential to delineating drug-induced dermatitis from stasis dermatitis. A thorough skin examination can elucidate the focal or extensive nature of the rash and is essential to making an accurate diagnosis. Immediate cessation of hydrochlorothiazide and switching drugs classes for hypertension management typically leads to resolution of symptoms.